Discourse on Women's Leadership in Islam: Asghar Ali Engineer's Thought Analysis Study - Adress Muhammad Adress Prawira Negara; Anita Juliani (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
The issue of women's leadership in Islam is still a determinant in various circles of scholars, both classical scholars, and modern scholars. However, with the presence of Islam on this earth, it will carry out its mission, justice, and experience. The purposes are to describe leadership from an Islamic perspective, to describe women's leadership from the Asghar Ali Engineer's perspective, and to analyze Asghar Ali Engineer's thinking about women's leadership. This study uses a qualitative method with a literature study approach. The data obtained were processed by description, interpretation, and analysis. The results of this study indicate that in the view of Asghar Ali Engineer, women are allowed to become leaders. As for the understanding of the classical scholars who forbid women to become leaders, Asghar Ali firmly said that the scholars did not see the social context when the verse was revealed so the interpretation that emerged was the distortion of gender issues.